Assessing the Accuracy and Efficiency of ICD-10 Coding Among Medical Billing Professionals in Outpatient Settings at Makkah region - Bukhari, Khadejah Mohammedalim; Bukhari, Rania Omar; Turkstani, Hind Abdulraheem; Turkstani, Daniyah Abdulraheem; alzahrani, shuruq fawaz; Aswani, Essa Ahmed; Alsolmei, Faten Aueed; Alharbi, Raed Hamed; Yahya, Rayan Ibrahim H; Alshehri, Abeer Ali (Journal of Posthumanism, 2024)
ICD-10 coding has been the gold standard for treatment and diagnosis documentation for modern health systems. Outpatient clinics, with high volumes of brief patient encounters, are especially dependent on timely and accurate coding. Errors in coding threaten reimbursement legitimacy and affect health analytics, illness tracking, and patient safety. This study investigated ICD-10 coding inefficiency and error trends by coding professionals in the outpatient setting. The study was performed in a sample of five hospitals at Makkah region , with a 100-subject pool of certified and non-certified coders. A survey tool was employed for measuring errors by type, coding speed, frequency of training, and utilization of automated coding software. Results indicated a frequent challenge in handling poor physician documentation, excessive software aids use accompanied by manual verification, and lack of formal refresher training. Coders with experience exceeding five years performed consistently higher for both speed and accuracy. The findings justify the need for improved interdisciplinary communication, coder education, and stricter requirements for software dependency. Investing in increased resources on these items would improve outpatient coding practice reliability considerably.